2007
DOI: 10.1002/jat.1215
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin induces mitochondrial membrane permeability and altered expression of cytochrome C in rat brain

Abstract: Deltamethrin is a type II synthetic pyrethroid insecticide and is used extensively. Numerous studies have demonstrated that deltamethrin can cause severe central nervous system symptoms. The mechanism of neuro-toxicity caused by deltamethrin is still poorly understood. This study investigated the effect of deltamethrin on the mitochondria-mediated apoptosis pathway in rat brain. The cortex and hippocampus mitochondrial membrane potential, permeability transition, expression of cytochrome c and activity of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In rodent models, deltamethrin further affected mitochondrial functions other than respiration. In particular, deltamethrin activated mitochondrial apoptotic pathways in rat brain cells [48] and disrupted steroid biosynthesis in mouse Leydig cells by causing mitochondrial membrane damage [49]. …”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, deltamethrin further affected mitochondrial functions other than respiration. In particular, deltamethrin activated mitochondrial apoptotic pathways in rat brain cells [48] and disrupted steroid biosynthesis in mouse Leydig cells by causing mitochondrial membrane damage [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroid pesticides have recently been reported to cause apoptosis (47), disrupt the endocrine system (48), change nitrogen metabolism (49), increase mitochondrial membrane permeability (50), and alter constitutive nitric oxide release (51). Higher SCE and MN frequencies and higher TOS plasma levels in our study confi rm the genotoxic and oxidative action of PM in human lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that organophosphates (Kashyap et al 2010), carbamates (Li et al 2015) and organochlorine (Kitazawa et al 2003) insecticides induce apoptosis through mitochondrial-dependent pathway, and similar indications were obtained in the present study. In vivo exposure of a synthetic pyrethroid -deltamethrin, have been shown to reduce mitochondrial cytochrome c levels (Chen et al 2007), and induce apoptosis through mitochondrial-independent pathway. Deltamethrin-induced apoptosis is initiated through a mitochondrial-independent pathway due to its interaction with Na + channels, leading to calcium overload and activation of the endoplasmic reticulum (ER) stress pathway (Hossain and Richardson 2011).…”
Section: Resultsmentioning
confidence: 99%